Penerapan Metode Tutor Sebaya dalam Meningkatkan Keterampilan Sosial Siswa Kelas IV SD - Alliyah Putri Supriyatna; Nurdinah Hanifah; I. Isrok’atun (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Improving the quality of human resources is quite crucial in this era. Basic education is the foundation for developing students' potential, therefore methods are needed in the learning process. One of them is the peer tutoring method. This research aims to find out how the peer tutoring method is applied, the obstacles experienced and determine the use of the peer tutoring method to improve students' social skills. The fact that this research was conducted in social studies learning, there were five class IV students at SDN Pakualam 02 South Tangerang who tended to be indifferent to the activities carried out because conventional methods such as lectures were still commonly used by teachers in social studies learning. Through this peer tutoring method, we are able to provide interesting learning so that students do not get bored easily in learning social studies and are able to improve their social skills to interact with their friends. Therefore, this research highlights the peer tutoring method as material for research and study. Qualitative descriptive methods were applied in this research with data in the form of information based on various findings in the field through observation, interviews and filling out process assessment questionnaires. Based on research findings, the application of the peer tutoring method showed positive changes in five students in forming groups during effective social studies learning, and could increase students' desire to be skilled at each other and solve problems understanding learning material together.